SOS – Simple orchestration of services - Queirós, Ricardo (2017)
Nowadays, we continue to write redundant code which can often be reused from the Web. Reusing programming tasks is beneficial since it speeds up the process of creating applications and reduces the errors related with the task creation from scratch. At the same time, the demands of our applications are increasing, leading to a simple problem having to be solved through several tasks. With the advent of the cloud, there are countless Web services that proliferate on the Web. One solution for developers is to use these Web Services. However, the process of mastering and coordinating all these services manually is time-consuming and error-prone. This paper presents SOS, a Simple Orchestration of Services. The ultimate goal of this tool is to act as a service composer while promoting the separation of concerns for two typical actors in this realm: the developer and the business analyst. The developer must define a service as a SOS task based on a JSON schema and submit it in a Web specialized editor. The business analyst uses the SOS editor, in an interactive way, to chain the required tasks to solve a specific problem. Then, the developer, uses a a simple client API – a SOS engine wrapper – to load a SOS manifest and to iterate over all tasks, without the need to dominate any bureaucratic aspects related with HTTP clients and messages. As a case study, several tasks are instantiated and aggregated in order to generate a composite service for a mobile app whose goal is to give an translated description of a picture taken with a mobile phone.